Carbene-catalyzed enantioselective annulation of dinucleophilic hydrazones and bromoenals for access to aryl-dihydropyridazinones and related drugs. Issue 25 (28th May 2021) - Mondal, Bivas; Maiti, Rakesh; Yang, Xing; Xu, Jun; Tian, Weiyi; Yan, Jia-Lei; Li, Xiangyang; Chi, Yonggui Robin
Abstract : Polarity inversion of arylidene hydrazones to react with bromoenals via carbene organic catalysis is disclosed. The reaction enantioselectively affords 6-aryl-4, 5-dihydropyridazinones and related drugs with proven commercial applications. Abstract : 4, 5-Dihydropyridazinones bearing an aryl substituent at the C6-position are important motifs in drug molecules. Herein, we developed an efficient protocol to access aryl-dihydropyridazinone molecules via carbene-catalyzed asymmetric annulation between dinucleophilic arylidene hydrazones and bromoenals. Key steps in this reaction include polarity-inversion of aryl aldehyde-derived hydrazones followed by chemo-selective reaction with enal-derived α, β-unsaturated acyl azolium intermediates. The aryl-dihydropyridazinone products accessed by our protocol can be readily transformed into drugs and bioactive molecules.